Vagal Withdrawal and Sympathetic Overactivity Contribute to the Genesis of Early-Onset Pregnancy-Induced Hypertension - G. K. Pal; P. Shyma; S. Habeebullah; Pravati Pal; Nivedita Nanda; P. Shyjus (International Journal of Hypertension)
Objective. In this study, we have assessed sympathovagal imbalance (SVI) by spectral analysis of heart rate variability (HRV) that contributes to the genesis of early-onset PIH. Methods. Body mass index (BMI), basal heart rate (BHR), blood pressure (BP) and HRV indices such as LFnu, HFnu, LF-HF ratio, mean RR, SDNN and RMSSD were assessed in normal pregnant women (Control group) and pregnant women having risk factors for PIH (Study group) at all the trimesters pregnancy. Retrospectively, those who did not develop PIH (Study group I) were separated from those who developed PIH (Study group II). Study group II was subdivided into early-onset and late-onset PIH. Sympathovagal balance (LF-HF ratio) was correlated with BMI, BHR and BP. Results. LF-HF ratio was significantly high in study group II compared to study group I and control group, and in early-onset PIH group compared to the late-onset category at all the trimesters of pregnancy, which was significantly correlated with BHR and BP. Alteration in HFnu in early-onset category was more prominent than the alteration in LFnu. Conclusion. Though the SVI in PIH is contributed by both sympathetic overactivity and vagal withdrawal, especially in early-onset type, SVI is mainly due to vagal inhibition.